The Least of These Political-Economic Dimensions of Roman Catholic Pastoral Theology - LaMothe, Ryan 1955- (2018)
While the emergence of Roman Catholic pastoral theology largely depended on moral and sacramental theologies, there is an often-neglected, yet important, source that has shaped and shapes pastoral theology in the Catholic Church. This article identifies and discusses this neglected root of Roman Catholic pastoral theology, namely the magisterium's political-prophetic critique of both the economic order, in particular capitalism, and the state vis-à-vis its role in addressing the survival and flourishing needs of individuals, families, and communities.
Keywords: Capitalism; Roman Catholic; Moral Theology; Pastoral Theology; Sacramental Theology